Sphenopalatine ganglion block for refractory COVID-19 headache: a descriptive case series - Felipe Chiodini Machado; Gilson Carone Neto; Rebeca Santiago Duarte Carone (Brazilian Journal of Anesthesiology, 2021)
Coronavirus SARS-CoV-2 is responsible for the COVID-19 pandemic, and headache is reported in 6.5% to 34% of all cases. There is little published evidence on the pharmacological treatment of COVID-19 headache. This case series presents six COVID-19 infected patients with refractory headache in which intranasal bedside Sphenopalatine Ganglion Block was performed for analgesia. All patients had a reduction in headache intensity from severe to mild or no pain after the procedure with minor transient side effects. Proposed mechanisms of action include reduction of local autonomic stimuli, intracranial vasoconstriction, and reduction of vasoactive substances release in the pterygopalatine fossa.